School Counselors' Self-Efficacy in Knowledge of the College Process. Issue 1 (2nd December 2020) - Nice, Matthew L.; Kolbert, Jered B.; Joseph, Matthew; Crothers, Laura M.; Hilts, Derron; Kratsa, Kristi
This study examined the self-efficacy of school counselors' college knowledge in the college process. Exploratory factor analysis revealed five characteristic factors: school counselors' knowledge related to the college application process, systems advocacy, direct services with disadvantaged populations, direct service with special populations, and coordination of college access events. Hierarchical regression analyses revealed that both school counselors' individual characteristics (e.g., years of experience, race/ethnicity, time engaged in advising, conducting lessons, and using technology and data) and ecological factors (e.g., school level, rate of college-going culture) were significant predictors of school counselors' self-efficacy for promoting college knowledge. We discuss implications for equity and school counselors' training.